Purnu 75. - Purnu 1975 (Helsinki : Artists' Association of Finland, 1975)
Aalto, Timo ; Ahigrén, Lauri ; Ahonen, Eino ; Artinaho, Hannu ; Granfelt, Erik ; Hakalahti, Juhani ; Hannula, Simo ; Hartman, Mauno ; Heikkilä, Erkki ; Heiskanen, Outi ; Hervo, Erkki ; Huhtamo, Kari ; Hyttinen, Niilo ; etc.
Purnu 75, Orivesi Pitkajarvi, 7.6 - 7.9.1975
boek
Keywords: Finland